Analysis of Halal Tourism Development at Sipamutung Temple and Its Impact on Community Welfare (Case Study in Padang Lawas Regency) - Hasibuan, Ulfa Rahmayani Assyfa; Chuzaimah Batu Bara; Waizul Qarni (Amkop Management Accounting Review (AMAR), 2025)
This study analyzes the potential for halal tourism development in Sipamutung Temple, Padang Lawas Regency, North Sumatra, and its impact on community welfare. Sipamutung Temple has high historical and cultural value, but it has not been optimally used as a halal tourist destination. The development of halal tourism in this temple has the potential to improve the local economy, create jobs, and reduce poverty. However, there are several challenges such as lack of infrastructure, limited promotion, and lack of halal facilities. This study uses a qualitative method with a SWOT analysis approach to identify strengths, weaknesses, opportunities, and threats in the development of halal tourism in Sipamutung Temple. The results of the study show that effective development strategies include infrastructure improvement, digital promotion, collaboration with third parties, and community empowerment through the creative economy and cultural events. With the support of the government and community participation, Sipamutung Temple has the potential to become a competitive leading halal tourist destination and make a real contribution to the welfare of the surrounding community .